Cortical and subcortical afferents to the amygdala of the rhesus monkey (Macaca mulatta). - Aggleton, J; Burton, M; Passingham, R (1980)
The afferent projections to the primate amygdala were studied using horseradish peroxidase. The potential advantages of this technique are discussed compared with those previously used to determine amygdaloid afferents. The findings indicate that certain agranular or dysgranular cortical regions may project directly to the amygdala: in particular, the orbital frontal cortex, anterior cingulate gyrus, subcallosal gyrus, temporal pole and anterior insula. These projections probably terminate predominantly in either the lateral or accessory basal nuclei. Other cortical projections from the inferotemporal and superior temporal gyri are described. Evidence was found for a heavy projection from the superior temporal sulcus to the lateral nucleus. Subcortical afferents were found from the hypothalamus, substantia innominata, diagonal band, thalamus, periaqueductal central gray, peripeduncular nucleus and from a band of cells extending medially from the peripeduncular nucleus to the midline, just ventral to the thalamus. In the thalamus, labelled cells were restricted to the non-specific nuclei, and were common in the rostral midline nuclei. No projection was observed from the dorsomedial nucleus of the thalamus. We discuss the implications of these results for interpreting the functions of the amygdala.